PENGARUH UPAH MINIMUM PROVINSI, INVESTASI DAN PDRB TERHADAP PENYERAPAN TENAGA KERJA DI INDONESIA - Sapriansah Ali Nur Iksan; Zainal Arifin; Muhammad Sri Wahyudi Suliswanto (Program Studi Ekonomi Pembangunan, 2020)
This study aims to describe the contribution and examine the effect of provincial minimum wages, investment and GRDP on labor absorption in Indonesia. The data used in this study uses panel data, namely a combination of time series and cross section, in this study using 34 provinces in Indonesia in 2013-2017. This study uses the Fixed Effect test. The results showed that the highest average contribution of labor absorption was in the province of East Java, investment was in the province of West Java, the provincial GDP and minimum wages were in the province of DKI Jakarta. Meanwhile, the estimation results show that the provincial minimum wage variable has a positive and significant effect on labor absorption, the investment variable has a negative and insignificant effect on labor absorption, while the GRDP variable has a positive and significant effect on labor absorption in Indonesia.